PERCEPTION OF ACADEMIC FRAUD BY THE SUBJECTS OF POSTGRADUATE EDUCATION (according to the results of a survey of undergraduates) - Сыздыкбаева, Айгуль; Улжаркын, Улжаркын (Pedagogy and Psychology, 2023)
The article examines the phenomenon of the spreading academic fraud of students. The authors identified factors related to academic dishonesty (promotion of cheating, low level of ethical standards; striving for success; risk-taking, financial consequences of course failure, psychological justification of the act). They presented three areas of qualification of the phenomenon under study, such as: taking, giving or receiving information from others; using prohibited materials, information, high-tech devices; bypassing the evaluation process. The practical significance of the study is the developed program for the diagnosis of academic fraud of subjects of postgraduate education. The program is based on the student research Murdock T. B., Stephens J. M. "Is cheating wrong? Students’ reasoning about academic». The author’s program uses two empirical research methods: questionnaires and analysis of products of activity. The questionnaire is anonymous, semi-closed, consists of 2 parts: introductory and main, the total number of questions of the questionnaire is 17. Essays of subjects of postgraduate education Part 3 of the program acts as a product of analysis. The number of samples is 102. The diagnostic results confirm the level of prevalence of academic fraud among the subjects of postgraduate education in Kazakhstan. In conclusion, measures, strategies, methods of preventing academic dishonesty at the university are presented on the example of foreign studies Gulli, 2007, Granitz & Loewy, 2007; Ridenour, 2007, Baxter & Boblin, 2007, Lanier, 2006 and others. In the article, academic fraud is considered through the concepts of academic deception, dishonest academic behavior, and fraud.